If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 213 + -1u = 143 Solving 213 + -1u = 143 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-213' to each side of the equation. 213 + -213 + -1u = 143 + -213 Combine like terms: 213 + -213 = 0 0 + -1u = 143 + -213 -1u = 143 + -213 Combine like terms: 143 + -213 = -70 -1u = -70 Divide each side by '-1'. u = 70 Simplifying u = 70
| 6-2(3x-1)=14 | | 1x-42=3x+4 | | (8/1)(6/2) | | 1/3p-8-p4 | | (10/5)(2/2) | | -w-11-3w=2w+4 | | f(x)=5x^2+2 | | 4-3(2+5v)+7= | | (X+3)27=90 | | 2x-3+2x-3+2x=114 | | 5x+2y-2z=-2 | | 10(3-4d)= | | (20/5)(2/2) | | 256=162-w | | 20s-45+14s-50=18s+18 | | 19-h+2h=-13 | | X-3x=-25 | | 27(x+3)=90 | | q+35+34q=44q+25 | | 14m+6n=10 | | (5a^2-5)/(6a-6) | | 4y-34+y+15=y+45 | | x+13.50=25.50 | | u+29+36u=24u+42 | | 33=-2+5w | | 3t-36+37=t+49 | | 35b-20+26b=45b+12 | | 2x+4y=278 | | 10q-1+8q-5=33 | | .20(119/105) | | c+24+3c=6c-23 | | 3x-7=5x-51 |